Diagnóstico Peatonal de la Carrera 8ª entre las Calles 16 y 18 de la Ciudad de Pereira-Risaralda - Arandia Fuquene, Ricardo Andres; Bocanegra Castaño, Alexandra (Universidad Antonio Nariño, 2023)
The research, titled was based on identifying issues along the four sidewalks in this section. These sidewalks are used daily by pedestrians commuting to work or engaging in activities within this city area. To achieve this, a descriptive-quantitative research approach was employed. Tools such as: drones and markers to indicate key measurement points were used, enabling the detection of obstacles and circumstances affecting pedestrian circulation.